Intelligent service oriented fog radio access network:principles, technologies and challenges - Chenxi LIU; Binghong LIU; Xian ZHANG; Xinnan LONG; Mugen PENG (智能科学与技术学报)
Big data and artificial intelligence has promoted the development of intelligent service.However, due to the high cost of data management and model training, as well as the increasing demands of users for latency and privacy, it is difficult to achieve the intelligent network based on the existing centralized network architecture.To address this issue, an artificial intelligence-based fog radio access network (AI-FRAN) architecture that supported distributed machine learning was proposed, and the fundamental principles that support the architecture were discussed.The key enabling techniques were identified that can realize the full utilization of communication resources, computing resources and cache resources in fog radio access network (F-RAN).Finally, the opportunities and challenges of AI-FRAN were discussed.